Notes on the ecology and distribution of the annual fern Anogramma leptophylla (L.) Link. (Pteridaceae) in Northern districts of Iraq - Ismail, A. M.; Maulood, B. K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2021)
The study involved the description of the environmental characters and distribution of Anogramma leptophylla (Annual Maidenhair fern) in Erbil and Garmian districts during May- 2017 in Kurdistan of Iraq. The geographical distribution of the taxa was recorded in Bani Bee region for the first time within the Garmian district but it was recorded before in the Zar Gali region within the Erbil district. The climatic characters of the studied site in Erbil district were: moist, cold and the elevation was up to 560 m above sea level with sandy clay soil texture whereas in the Garmian district: dry, hot, and the elevation was only 330 m above sea level with sandy stone soil. Plant up to 13 cm long, megaphyllous, fronds compound 3-6 cm long, divided into alternate petiolate pinnae. In the present work, some ecological, morphological, and geographical distribution for A. leptophylla is described for the first time in the Iraqi Kurdistan region.